ATUAÇÃO FISIOTERAPÊUTICA EM PACIENTES COM SÍNDROME DE GUILLIAN BARRÉ EM USO DE IMUNOGLOBULINA HUMANA (REMUNOM, 2024)
Guillian Barré Syndrome (GBS) is characterized as a progressive, chronic, autoimmune disease that slowly affects the nervous system, leaving the individual with some movement limitations and directly affecting the neuromuscular system. GBS can be treated with medication or physiotherapy, in addition to plasmapheresis, which is a therapy that removes substances from the plasma that affect the immune system, and intravenous infusion of immunoglobulins. The aim of this study was to analyze the physiotherapeutic approach to Guillain-Barré Syndrome in patients using human immunoglobulin. This is a systematic literature review, with data collected from scientific articles published in electronic databases: Virtual Health Library (VHL), Scientific Electronic Library Online (SCIELO), Physiotherapy Evidence Database (PEDro) and PubMed. It was concluded that the use of human immunoglobulin in conjunction with physiotherapy is extremely important for the recovery of GBS patients, especially when used early depending on the patient's clinical stage.